Design and implementation of a novel general format multimedia digital rights management system - Qin-long HUANG; Zhao-feng MA; Jia MO; Xin-xin NIU; Yi-xian YANG (Tongxin xuebao)
Aiming at the copyright protection of multimedia content,a novel general format multimedia digital rights management model was designed which includes encryption and packaging of content,ke nagement,security engine,license management and distribution,DRM client,DRM management and other functional units.This model uses un-structured encryption method which overcomes the limit ions of encryption method based on the content format to sup-port the general format multimedia.In addition,this model uses the license acquisition number as the only certificate to download license to solve the problem of license reissue and transfer,and supports fine-grained control model.Combined with this model,a multimedia digital rights management system was developed based on fixed and mobile converged services which is used in the field of digital consumer.experimental results and practical application show that this scheme with good practice in the copyright protection multimedia content does not affect the multimedia quality,and have high efficiency and safety.